Apatinib inhibits cell proliferation and migration of osteosarcoma via activating LINC00261/miR-620/PTEN axis. Issue 18 (17th September 2021) - Han, Gang; Guo, Quanyi; Ma, Ning; Bi, Wenzhi; Xu, Meng; Jia, Jinpeng
ABSTRACT: Apatinib has been recently identified as a potential treatment option for osteosarcoma (OS). Nonetheless, the molecular mechanism of Apatinib in regulating OS progression remains unclear. To explore the downstream molecules that mediated the tumor-suppressive effect of Apatinib on OS. Expression levels of genes were detected by RT-qPCR and western blot assays. Functional assays including Transwell assay were applied to detect the proliferation, apoptosis and migration of OS cells. Molecular interactions were detected by luciferase reporter assay and RIP assay. Apatinib inhibited the proliferation and migration of OS cells. LINC00261 was down-regulated in OS cells but then up-regulated after the treatment by Apatinib. Silencing LINC00261 abrogated the suppressive effect of Apatinib on OS cell proliferation and migration. MicroRNA-620 (miR-620) could be sponged by LINC00261. Besides, miR-620 was up-regulated in OS cells and Apatinib treatment reduced miR-620 expression. Furthermore, LINC00261 acted as a competitive endogenous RNA (ceRNA) by sequestering miR-620 to up-regulate the expression of phosphatase and tensin homolog (PTEN). Moreover, Apatinib hindered in vitro cell proliferation and migration as well as the in vivo tumorigenesis of OS through LINC00261/miR-620/PTEN axis. Apatinib-enhanced LINC00261 restrained OS via miR-620/PTEN axis, indicating LINC00261 might promote the efficacy of Apatinib on OS.